Diversity of arthropods communities in transgenic cotton varieties in Santa Fe province, Argentina - Sosa, Maria Ana; Almada, Melina Soledad (Universidad Nacional de La Plata, 2018)
Genetically modified (GM) crops have been widely expanded within the agricultural systems in Argentina, being BT/ RR cotton well adopted since its commercial approval in 2009. However no has been study and compared the arthropods diversity in cotton crops Bt and non Bt with one and two stackes trait events and its possible impacts on the environment. The aim of this study was to compare single-trait event cotton (non Bt) to stacked trait event cotton (Bt) evaluating abundance, richness and diversity of arthropod for the environmental conditions of the northern region of Santa Fe and to obtain information useful for Integrated Pest Management (IPM) Programs. Experiments were conducted during three growing seasons (Y1: 2009/10, Y2: 2010/11 and Y3: 2011/12) at the Agricultural Experimental Station of INTA Reconquista, Santa Fe (Argentina). A randomized complete block design with five replications was used with two Treatments: 1) No Bt: (RR) G2000, herbicide resistant and 2) Bt Crop: (BR) NuOpal, Lepidoptera and herbicide-resistant, using two sampling methods (pitfall traps and G-Vac). The abundance and species richness showed no differences between the Bt and non Bt cotton and years analyzed, except for the diversity index did show differences between Y1 and Y2. A high proportion of beneficial arthropods were recorded for both treatments throughout the entire sampling period. According to the results obtained in three cotton seasons, the diversity of arthropods present in both events cotton crops were not affected and may be considered as a control strategy in a IPM for maintaining this fauna and sustainability in this crops.